Circulating miRNAs as surrogate markers for circulating tumor cells and prognostic markers in metastatic breast cancer - Madhavan, Dharanija; Wallwiener, Markus; Cuk, Katarina; Modugno, Caroline; Scharpff, Martina; Schott, Sarah; Heil, Jörg; Turchinovich, Andrey; Yang, Rongxi; Benner, Axel; Trumpp, Andreas; Sohn, Christof; et al. (Clinical cancer research, 2012)
Purpose: The use of circulating tumor cells (CTC) as a prognostic marker in metastatic breast cancer (MBC) has been well established. However, their efficacy and accuracy are still under scrutiny mainly because of methods of their enrichment and identification. We hypothesized that circulating miRNAs can predict the CTC status of patients with MBC, and tested for the same. Furthermore, we aimed at establishing a panel of circulating miRNAs capable of differentiating MBC cases from healthy controls. Experimental Design: Circulating miRNAs from plasma of CTC-positive and CTC-negative patients with MBC, and healthy controls, were profiled by TaqMan Human MicroRNA arrays. Candidates from the initial screen were validated in an extended cohort of 269 individuals (61 CTC-positive, 72 CTC-negative, 60 CTC-low MBC cases, and 76 controls). Results: CTC-positive had significantly higher levels of miR-141, miR-200a, miR-200b, miR-200c, miR-203, miR-210, miR-375, and miR-801 than CTC-negative MBC and controls (P < 0.00001), whereas miR-768-3p was present in lower amounts in MBC cases (P < 0.05). miR-200b was singled out as the best marker for distinguishing CTC-positive from CTC-negative patients (AUC 0.88). We identified combinations of miRNAs for differentiating MBC cases from controls (AUC 0.95 for CTC-positive; AUC 0.78 for CTC-negative). Combinations of miRNAs and miR-200b alone were found to be promising prognostic marker for progression-free and overall survival. Conclusion: This is the first study to document the capacity of circulating miRNAs to indicate CTC status and their potential as prognostic markers in patients with MBC. Clin Cancer Res; 18(21); 5972-82. ©2012 AACR.